Naming the Ineffable: St. Thomas Aquinas’s Teaching on the Divine Names - Stefańczyk, Andrzej (Przegląd Tomistyczny, 2025)
The key issue of this paper is the question of whether we can formulate affirmative (positive) judgments about God. This issue is rooted in the assertions of Aquinas himself, who says that we can know that God is (an sit), but we do not know what He is (quid sit). Although St. Thomas draws considerably on the legacy of Neoplatonic thought, he clearly modifies it and introduces his own solutions to certain issues in defiance of Platonic and Neoplatonic “orthodoxy.” The general thesis of this article is that Aquinas seeks to rework Neoplatonic content by applying to it Aristotelian instrumentarium. More detailed analysis concerns the divine names, which Thomas discusses in q. 13 of his theological Summa and in his Exposition on The Divine Names by Pseudo-Dionysius the Areopagite, where this problem not only receives a profound interpretation in terms of semantics, but above all in terms of metaphysics. Aquinas, therefore, incorporates some elements of Neoplatonism into his teaching, but modifies them guided by at least three criteria: (i) the requirement of orthodoxy (in line with the professed religion), (ii) the accepted standards of the “modern science” of the time i.e. the paradigm of the Aristotelian theory of science, (iii) the condition of the coherence of the system, which requires the system to be free from logical contradictions. Thomas’s modifications arise in general from his objective, which is divergent from that of Dionysius, and from the method adopted by Thomas in explaining philosophical and theological problems. The goal for the Areopagite is mystical union with God, while for Thomas it is instruction in, and explanation of, the sacra doctrina, i.e. the body of human knowledge concerning the revelation (DeDivNom, pr.); Thomas’s method aims at greater precision in speaking and explaining the “sacred doctrine” using Aristotelian instrumentarium. [...]